Analisis Potensi Usaha Rumah Tangga (Home Industri) Emping Melinjo Di Kecamatan Kampung Melayu Kota Bengkulu - Duharman Duharman; Erwani Yusuf; Mutia Alinsyah Putri (Jurnal Multidisiplin Dehasen (MUDE), 2024)
This study aims to determine the potential of emping melinjo home industry in Kampung Melayu District, Bengkulu City. This study was conducted in Kampung Melayu District, Bengkulu City using a qualitative research approach and type. Data sources from emping melinjo business owners. Data collection techniques used observation, interviews and documentation. The data analysis used in this study includes reviewing all data, data reduction, presenting data and drawing conclusions. Checking the validity of the data includes extension of participation, observer persistence, and source triangulation. The results of the study showed the potential for home industry of melinjo chips in Kampung Melayu District, Bengkulu City, there are several potentials, namely determining the capital spent to produce melinjo chips, the availability of raw materials purchased from the same area, namely Enggano, human resources, namely one business owner who has employees and 2 business owners only produce it themselves without the help of human labor, Then to support the production of melinjo chips in the form of marketing carried out by business owners, income from melinjo chips and also getting profit from the home industry of melinjo chips. By improving product quality and marketing, this business has the potential to grow, provide benefits to the community and become a source of sustainable income.